Long Noncoding RNA LINC00472 Inhibits Proliferation and Promotes Apoptosis of Lung Adenocarcinoma Cells via Regulating miR-24-3p/DEDD. (31st August 2018) - Su, Chongyu; Shi, Kang; Cheng, Xu; Han, Yi; Li, Yunsong; Yu, Daping; Liu, Zhidong
Objective: We aimed to detect the role of LINC00472 via regulating miR-24-3p and death effector domain-containing DNA-binding protein in lung adenocarcinoma. Methods: Long noncoding RNA, microRNA, and messenger RNA levels were determined using reverse transcription quantitative polymerase chain reaction. The expression of death effector domain-containing DNA-binding protein was determined using Western blot assay. 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay and colony formation assay were conducted to explore the proliferation of cells. The cell apoptosis was tested by flow cytometry assay. Target relationships between miR-24-3p, death effector domain-containing DNA-binding protein, and LINC00472 were validated by dual-luciferase reporter gene assay. Results: LINC00472 and death effector domain-containing DNA-binding protein were found to be underexpressed, whereas miR-24-3p was found overexpressed in lung adenocarcinoma cell lines and tissues. Both LINC00472 and death effector domain-containing DNA-binding protein can bind to miR-24-3p. Overexpression of LINC00472 led to higher death effector domain-containing DNA-binding protein level, demoting cell proliferation while promoting apoptosis. Overexpression of miR-24-3p reduced death effector domain-containing DNA-binding protein level, which facilitated cell proliferation and inhibited cell apoptosis, as well as to some extent restrained the effects of LINC00472. The high expression of miR-24-3p in tumor cells was negatively related to LINC00472 and death effector domain-containing DNA-binding protein, whereas the expression of LINC00472 and that of death effector domain-containing DNA-binding protein were positively correlated. Conclusion: Our findings suggested that LINC00472 contributed to the increase in lung adenocarcinoma cell apoptosis and the inhibition of proliferation via regulating miR-24-3p/ DEDD, which might provide a novel insight into potential therapeutic approach for lung adenocarcinoma.